Study on nutrition requirements and effect of different diets on gonadic and somatic growth of beluga (Huso huso) in new condition such as inland brackish water - Alizadeh, Morteza; Sepahdari, A.; Rajabipour, F.; Sarsangi, H. (Iranian Fisheries Science Research Institute, 2008)
Taking into consideration culture of beluga (Huso huso) in new condition such as inland brackish water, it is very important to study nutrition requirements and effect of different diets on gonadic and somatic growth as well as physiological condition. In this research 74 beluga (4 years old) cultured in brackish water earth ponds in Bafgh fisheries research station, were selected and distributed in 8 circular cement ponds. Feeding was done in 4 formulated diets with fixed protein level and 4 energy levels (400,425,450,475 kcal/100gr). Samples were biopsied in the first and the end of experiment to determine sexuality and stage of maturation. To study gonad tissues, the hematoxylin-eosin method was used. Results indicated that somatic and gonadic growth index was affected by diets. Growth somatic overlapped in both sexes. Sexual maturation stages were not the same in both males and females and transition from stage II in males was more rapid than females. Considering the results in this study, diet treatments influenced on somatic growth in both sexes and gonadic growth in females. It seems to state of somatic and especially gonadic growth in brackish water is suitable. Therefore, inland brackish water environment can be introduced as a suitable environment cultivation of beluga.